(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aims to analyse the Influence of TikTok Social Media Marketing and Fear of Missing Out (FOMO) on impulsive buying among Generation Z in Garut Regency. The Research method used is a descriptive, verifiable, quantitative method with a sample size of 250 respondents. Data analysis techniques use Partial Least Squares-based Structural Equation Modelling SEM-PLS. The results of the study indicate that TikTok Social Media Marketing and FOMO have a positive and significant effect on impulsive buying, both partially and simultaneously. These findings emphasise the importance of responsible management of digital marketing strategy.